Pengaruh Motivasi Terhadap Kinerja Pegawai Pada Dinas Pertambangan Dan Energi Kab. Kutai Kartanegara - Umar, Nasir (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2008)
The motivation effect to  the employee work at mining department in department of mining and energy of Kutai Kartanegara Regency, according to the research result and data analysis result can be known theoretically to know account result with product moment correlation formula gotten correlation score as 0.933. this result include into very strong interpretation category, according to the interpretation table of correlation score, the account result can be concluded that there is positive and significant relation between motivation variable and employee ability variable to the Department of mining and energy of Kutai Kartanegara that motivation has effect to the employee work in Department of mining and energy of Kutai Kartanegara Regency accepted because of the truth has been proven. Kata Kunci :  Motivation, Works